Ovitrap Surveillance of Aedes aegypti and Aedes albopictus in Dengue Endemic Areas in Keramat and Shah Alam, Selangor in 2016 - A, Noor Afizah; AK, Mohd Arif; WA, Nazni; HL, Lee (IIUM Medical Journal Malaysia, 2018)
Introduction: Entomological surveillance is crucial to determine the abundance of dengue vector and to evaluate breeding areas of Aedes aegypti and Aedes albopictus. The objective of this study is to determine the distribution and breeding preference for both Ae. aegypti and Ae. albopictus in dengue endemic areas. Materials and Methods: Ovitraps surveillance was conducted in two dengue endemic areas; AU2, Keramat and Seksyen 7, Shah Alam, Selangor. A minimum number of 100 ovitraps were deployed for 5 days in the study sites. Samples collected were brought back to the lab and all larvae recovered were identified to species level. Results: The ovitap index (OI) in both localities exceeded the transmission threshold of 10% with the OI recorded ranged from 42.3-79.8% in AU2, Keramat and 16.7-42.9% in Seksyen 7, Shah Alam. Ae. albopictus was the dominant species in AU2 Keramat with the highest ratio Ae. aegypti to Ae. albopictus recorded was 1.00:22.79. Nonetheless, in Seksyen 7, Shah Alam the difference in Ae. aegypti to Ae. albopictus ratio is not really prominent with 1.00:3.61 for ovitraps deployed outdoor and 3.40:1.00 for ovitraps set indoor. It was determined that single infestation of either Ae. aegypti or Ae. albopictus is more frequent for ovitraps deployed indoor and/or outdoor, respectively. It was also determined that mixed infestations were found in this study indicating that both species can oviposit in the same container. Conclusion: This study indicates that OI is still above transmission threshold in both study sites. While Ae. aegypti and Ae. albopictus remain as a dominant indoor and outdoor breeder, respectively, mixed breeding of Aedes species in a same container was also observed.